Classroom teachers' online teaching experiences during the COVID-19 pandemic: The perspective of technological pedagogical content knowledge - Mehmet Hayri Sarı; Hilal Keser (Journal of Pedagogical Research, 2021)
This qualitative study aims at evaluating the online teaching experiences of classroom teachers during the New Coronavirus Disease (COVID-19) period in terms of the Technological Pedagogical Content Knowledge (TPACK). The interviews were conducted with 17 classroom teachers within the scope of the current research. The data were collected via open-ended semi-structured interview questions. As a result of the analysis of the data, the classroom teachers considered themselves competent in the components of Technological Knowledge (TK), Content Knowledge (CK), Pedagogical Knowledge (PK) and Pedagogical Content Knowledge (PCK), they did not consider themselves competent in the Technological Content Knowledge (TCK) and Technological Pedagogical Knowledge (TPK) components, which were the result of the integration of these components with technology. When the participants were addressed in terms of the online teaching experiences, technology uses, competencies and professional training needs as a whole during the COVID-19 period, it was found that they did not use digital tools primarily for pedagogical purposes. Therefore, the teachers needed extensive pedagogical support when designing digital teaching. All of these results suggest that 21st century teachers need to develop their knowledge and skills in terms of CK, PK, TCK, and TPK that emerge with the transfer of such knowledge to technological processes and TPACK that forms the intersection of all information.